2009
DOI: 10.1111/j.1750-3639.2008.00194.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Altering Aβ Distribution from the Brain to the Vasculature Ameliorates Tau Pathology

Abstract: The inheritance of the ε4 allele of the apolipoprotein E (apoE) gene is the major genetic risk factor for developing late-onset Alzheimer disease. In transgenic mice overexpressing amyloid precursor protein (APP), replacing the endogenous mouse apoE gene with the human apolipoprotein E4 (apoE4) gene alters the distribution of amyloid-β (Aβ) deposits from the brain parenchyma to the vasculature. However, the effects of this distribution on the onset and progression of tau pathology remain to be established. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 49 publications
0
26
2
Order By: Relevance
“…We have previously shown that A␤ accumulation facilitates Tau pathology and that this can occur via different mechanisms (45,49,(75)(76)(77). Here, we propose that A␤ may also facilitate Tau accumulation by increasing mTOR activity.…”
Section: Discussionmentioning
confidence: 79%
“…We have previously shown that A␤ accumulation facilitates Tau pathology and that this can occur via different mechanisms (45,49,(75)(76)(77). Here, we propose that A␤ may also facilitate Tau accumulation by increasing mTOR activity.…”
Section: Discussionmentioning
confidence: 79%
“…How Aβ mediates alteration and aggregation of Tau is uncertain, although three major mechanisms have been proposed: (i) Aβ activates kinases that phosphorylate Tau (Hernández & Avila, 2010; Llorens‐Martín et al ., 2014) altering its capacity to bind tubulin; (ii) Aβ alters the proteasomal degradation of Tau, increasing its concentration in free state (Oddo et al ., 2009); (iii) Aβ intracellular aggregates have a nucleation effect on Tau (Guo et al ., 2006; Bolmont et al ., 2007). The third hypothesis is supported by the occurrence of Tau pathology in different types of cerebral amyloidosis (Holton et al ., 2001; Giaccone et al ., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Together with aberrant Aβ deposits in the neuropil, a genetic basis is essential in influencing the onset and/or modifying the progression of the disease. 7 Genomic factors…”
Section: Introductionmentioning
confidence: 99%